2021
DOI: 10.1128/jvi.00919-21
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Taxonomic Properties of the Newly Isolated Cotonvirus japonicus , a New Lineage of the Subfamily Megavirinae

Abstract: Since 2003, various viruses from the subfamily Megavirinae in the family Mimiviridae have been isolated worldwide, including icosahedral mimiviruses and tailed tupanviruses. To date, the evolutionary relationship between tailed and non-tailed mimiviruses has not yet been elucidated. Here, we present the genomic and morphological features of a newly isolated giant virus, Cotonvirus japonicus (cotonvirus), belonging to the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Various CPEs have been reported, including cell rounding, lysis, aggregation, and cyst formation ( 8 12 ). Most of the viruses that infect Acanthamoeba cause cell rounding in the late stages of infection, and then some viruses lead to cell lysis ( 8 , 10 13 ). It has also been reported that tupanvirus ( Mimiviridae ) and hokutovirus ( Marseilleviridae ) cause cell aggregation before cell rounding ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various CPEs have been reported, including cell rounding, lysis, aggregation, and cyst formation ( 8 12 ). Most of the viruses that infect Acanthamoeba cause cell rounding in the late stages of infection, and then some viruses lead to cell lysis ( 8 , 10 13 ). It has also been reported that tupanvirus ( Mimiviridae ) and hokutovirus ( Marseilleviridae ) cause cell aggregation before cell rounding ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the phylogenetic position of Me. baoshan in the family Mimiviridae , molecular phylogenetic analysis was performed based on NCLDV core genes, including major capsid protein, family B DNA polymerase, D5-like primase-helicase, transcription factor S-II, and virion packaging ATPase ( Assis et al, 2017 ; Abrahão et al, 2018 ; Takahashi et al, 2021 ). Me.…”
Section: Resultsmentioning
confidence: 99%
“…Members of Mimiviridae can be divided into several lineages, including lineage A (represented by APMV, La Scola et al, 2003 ), B (Acanthamoeba polyphaga moumouvirus, Yoosuf et al, 2012 ), C (Megavirus chiliensis, Arslan et al, 2011 ), and Tupanvirus ( Abrahão et al, 2018 ), based on the phylogenetic analysis of conserved genes, like major capsid protein, family B DNA polymerase, D5-like primase-helicase, etc. New lineage has been proposed due to the isolation of new viruses ( Takahashi et al, 2021 ). Using different gene or gene set may result in slightly different topology in the phylogenic tree, but the lineage classification remains unchanged ( Arslan et al, 2011 ; Yoosuf et al, 2012 ; Assis et al, 2017 ; Abrahão et al, 2018 ; Takahashi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 The VF in which nucleic acids accumulate due to active transcription and replication increases in size and neosynthesized virions start budding at its periphery, recycling host cell membranes derived from the ER, 44,79,80 or Golgi compartments, as recently described for Cotonvirus (clade E). 81 The last step in virion maturation, after genome loading into the nucleoid, is the addition to the capsid of the fibril layer, which comprises many proteins and two different polysaccharides (section 3.2.2). 80,82 Hundreds of neosynthesized virions are released after cell lysis.…”
Section: Family Mimiviridaementioning
confidence: 99%